Identification of Low‐Abundance Urinary Biomarkers in Lupus Nephritis Using Electrochemiluminescence Immunoassays. Issue 5 (3rd April 2019) - Stanley, Samantha; Mok, Chi Chiu; Vanarsa, Kamala; Habazi, Deena; Li, Jennifer; Pedroza, Claudia; Saxena, Ramesh; Mohan, Chandra
Abstract : Objective: To investigate the utility of a sensitive platform using electrochemiluminescence (ECL) for the identification of low‐abundance urinary protein biomarkers in lupus nephritis (LN). Methods: Forty‐eight urine samples were obtained from subjects in 2 independent cohorts, each consisting of 3 groups (matched for age, sex, and race) of 8 patients with active LN (renal Systemic Lupus Erythematosus Disease Activity Index [SLEDAI] >0), 8 patients with inactive SLE (renal SLEDAI 0), and 8 healthy controls. Samples were tested using a preexisting 40‐plex ECL panel. A custom 5‐plex ECL panel was then developed for further validation studies and used to test 140 urine samples (from 44 patients with active LN, 41 patients with inactive SLE, 28 healthy controls, and 27 patients with other kidney diseases). Results: Levels of 17 urinary proteins were elevated ( P < 0.05 by 2‐tailed Mann‐Whitney U test) in samples from patients with active LN compared to samples from patients with inactive SLE and healthy controls in cohort 1, while 9 were similarly elevated in cohort 2. Of these, interleukin‐7 (IL‐7), IL‐12p40, IL‐15, interferon‐γ–inducible protein 10 (IP‐10), and thymus and activation–regulated chemokine (TARC) were chosen for further validation. These 5 proteins were undetectable by enzyme‐linked immunosorbent assay (ELISA). Hence, a custom 5‐plex ECL panel was developed and used to validate the results from the initial 40‐plex screening panel. Urinary IL‐7, IL‐12p40, IL‐15, IP‐10, and TARC levels were again significantly elevated in patients with active LN compared to those with inactive SLE and healthy controls, and correlated well with the renal SLEDAI and physician's global assessment of disease activity (R > 0.67, P < 0.05). All 5 urinary proteins were more frequently elevated in LN compared to controls with other chronic kidney diseases, although overall group differences attained significance only for urinary IL‐7 and IL‐15. Conclusion: Urinary levels of IL‐7, IL‐12p40, IL‐15, IP‐10, and TARC are potentially useful diagnostic tools in LN. The use of ECL assays may allow detection of urinary biomarkers that are below ELISA detection limits.